PENGARUH KEMAMPUAN DAN MOTIVASI KERJA DOSEN TERHADAP KUALITAS LAYANAN KEPADA MAHASISWA - ., Supriyanto (Manajemen Bisnis, 2011)
Universitas Kanjuruan MalangE-mail : ian_priyanto@yahoo.comABSTRACTReffering to the demands of public service quality, the higher level education as one of publicservice institutions is hard facing their challenges. Its challenges is a competitiveness. So, It isneeded the service quality to the student for facing its competitiveness. This research is conducted toknow the influential of Lecturers' competencies and job motivation to the students' services.Analyses method uses regression analyses. Data collection uses questionaires which is given to64 lecturers as the respondents. They are chossen from 132 lecturers that is relevant as randomsampling.The result of research shows that (1) lecturers' competencies has significant influence to theservice quality for students, (2) teaching motivations is also significant influencial to the servicequality for students, (3) lecturers' competencies has relationship to the motivation for teaching and(4) lecturer's competencie and motivations simultaneously significant influence to the servive qualityfor the students.Keywords: competency, motivations, service quality, lecturers